Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1097/01.wcb.0000127161.89708.a5
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Transfection via Herpes Simplex Virus Blocks Apoptosis-Inducing Factor Translocation after Focal Ischemia in the Rat

Abstract: Apoptosis plays a critical role in many neurologic diseases, including stroke. Cytochrome c release and activation of various caspases are known to occur after focal and global ischemia. However, recent reports indicate that caspase-independent pathways may also be involved in ischemic damage. Apoptosis-inducing factor (AIF) is a novel flavoprotein that helps mediate caspase-independent apoptotic cell death. AIF translocates from mitochondria to nuclei where it induces caspase-independent DNA fragmentation. Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 76 publications
7
64
1
Order By: Relevance
“…An increase in AIF in the cytosolic fraction and a decrease in the mitochondrial fraction have been reported by 8 hours of permanent ischemia (Zhao et al, 2004). However, in the present study, AIF was undetectable in the cytosolic fraction and was unchanged in the mitochondrial fraction.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…An increase in AIF in the cytosolic fraction and a decrease in the mitochondrial fraction have been reported by 8 hours of permanent ischemia (Zhao et al, 2004). However, in the present study, AIF was undetectable in the cytosolic fraction and was unchanged in the mitochondrial fraction.…”
Section: Discussioncontrasting
confidence: 55%
“…Progressive increases in nuclear AIF have also been reported over 48 hours of permanent distal MCAO in the rat (Zhao et al, 2004). A recent study in mice reported progressive increases in nuclear AIF over the first 24 hours of permanent MCAO, and the increase observed at 4 hours was attenuated by an antioxidant (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The ischemic penumbra was defined as the tissue saved by hypothermia 2 days post-stroke, and the corresponding region from the control ischemic brain was dissected for comparison. Whole cell protein was extracted from the fresh brain tissue, and Western blot was performed as described with modification [14,17,18]. In each lane 20 μg protein was subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) using 4-15% Ready Gel (BIO-RAD Laboratories, Cat# L050505A2) for 1.5 hours.…”
Section: Western Blotsmentioning
confidence: 99%